Organizational Performance in Electronic-Based Public Services at the Class II Baubau Harbor Master and Port Authority Office - Muhammad Syukri; Asmiddin, Asmiddin; Andi Tendri (Sean Institute, 2025)
This study aims to describe organizational performance including Quality, Quantity, Timeliness, Effectiveness, Independence and Work Commitment and describe electronic-based public services including SPBE Objectives, Non-Corruption SPBE, SPBE Costs and Time, SPBE Scope, SPBE Mandatory and SPBE Principles. This study uses a qualitative descriptive design that collects data by means of observation, interviews with informants. The data is tabulated as needed and then the data is analyzed qualitatively descriptively including data reduction, data presentation and drawing conclusions so that it can produce an understanding and is proven by data analysis techniques and the validity of the data findings. The results of this study indicate that to see Organizational Performance at the Baubau Class II Harbormaster and Port Authority Office according to Robbins (2006) in Sebayang (2017) is formed from six Indicators, namely: a) Quality of work; b). Quantity of work; c). Timeliness; d). Effectiveness; f). Commitment. to maintain membership and electronic-based public services at the Baubau Class II Harbormaster and Port Authority Office according to Presidential Regulation (Perpres) Number 95 of 2018 including: a). SPBE objectives; b). Non-corruption of SPBE; c). SPBE costs and time; d). SPBE scope; e). SPBE mandatory; f). SPBE principles. Suggesting for further research to be improved by completing administrative documents and always conducting socialization and implementation of policies, and continuing to monitor and evaluate SPBE for service users.